Research on Customer Requirement-Driven Individualized Product Module Division and Configuration Based on Community Structure - Qin Yang; Xuzheng Li; Qunqun Yin; Fan Liu; Weijie Chang (Advances in Mathematical Physics)
The main goal of designing individualized products is to meet the specific requirements presented by the customer. Therefore, designers need to adapt the relevant components of the product for each customer, which is difficult to achieve efficiently with existing methods. In this paper, we propose an integrated approach that enables intuitive modelling of products and supports fast conversion of different customer requirements (CRs) to configuration solutions. Firstly, the product properties are decomposed, and a standardized CR expression template is established to enable the mapping of CR information to product properties change information. Secondly, the community structure in complex network theory is introduced to visualize and quantitatively describe the relationship between product parts. The community detection method based on fuzzy clustering is applied to module division, and the optimal result is obtained using the F-statistic and modularity as evaluation indexes. Finally, the individualized product configuration problem is transformed into a dynamic constraint satisfaction problem. According to CR information and product module division result, the hierarchical community structure is used to narrow the search space and quickly derive solutions with high customer satisfaction through case-based configuration. An automatic guided vehicle is used as an example to illustrate the effectiveness and practicality of this approach.